Effective retardation factor for transport of reactive solutes in highly heterogeneous porous formations. Issue 12 (3rd December 2013) - Maghrebi, Mahdi; Jankovic, Igor; Fiori, Aldo; Dagan, Gedeon
<x xml:space="preserve">Abstract</x> [1] The effective retardation factor of highly heterogeneous porous formations is investigated using an analytical derivation and numerical simulations based on the self‐consistent approximation and the multi‐indicator conductivity model, used in the past for the effective hydraulic conductivity estimation. Both positive and negative correlation between the logarithm of hydraulic conductivity K and the logarithm of sorption distribution coefficient Kd are investigated, including the effects of random noise. The arithmetic average of the random retardation factor is found to represent accurately the effective retardation factor of isotropic and anisotropic formations regardless of correlation between ln Kd and ln K, and for variance of ln K as large as 8.